Genomic and physiological analyses of 'Reinekea forsetii' reveal a versatile opportunistic lifestyle during spring algae blooms. (3rd February 2017) - Avcı, Burak; Hahnke, Richard L.; Chafee, Meghan; Fischer, Tanja; Gruber‐Vodicka, Harald; Tegetmeyer, Halina E.; Harder, Jens; Fuchs, Bernhard M.; Amann, Rudolf I.; Teeling, Hanno
Summary: Gammaproteobacterial Reinekea spp. were detected during North Sea spring algae blooms in the years 2009‐2012, with relative abundances of up to 16% in the bacterioplankton. Here, we explore the ecophysiology of 'R. forsetii' strain Hel1_31_D35 that was isolated during the 2010 spring bloom using (i) its manually annotated, high‐quality closed genome, (ii) re‐analysis of in situ data from the 2009–2012 blooms and (iii) physiological tests. High resolution analysis of 16S rRNA gene sequences suggested that 'R. forsetii' dominated Reinekea populations during these blooms. This was corroborated by retrieval of almost complete Hel1_31_D35 genomes from 2009 and 2010 bacterioplankton metagenomes. Strain Hel1_31_D35 can use numerous low‐molecular weight substrates including diverse sugar monomers, and few but relevant algal polysaccharides such as mannan, α‐glucans, and likely bacterial peptidoglycan. It oxidizes thiosulfate to sulfate, and ferments under anoxic conditions. The strain can attach to algae and thrives at low phosphate concentrations as they occur during blooms. Its genome encodes RTX toxin and secretion proteins, and in cultivation experiments Hel1_31_D35 crude cell extracts inhibited growth of a North Sea Polaribacter strain. Our data suggest that the combination of these traits make strain Hel1_31_D35 a versatile opportunist that is particularly competitive during spring phytoplankton blooms.